Je suis un monstre qui vous parle: rapport pour une académie de psychanalystes - Preciado, Paul B. (Grasset, 2020)
« La psychanalyse est face à un choix historique sans précédent : soit elle continue à travailler avec l'ancienne épistémologie de la différence sexuelle et légitime de facto le régime patriarco-colonial qui la soutient, devenant ainsi responsable des violences qu'elle produit, soit elle s'ouvre à un processus de critique politique de ses discours et de ses pratiques. Continuer à pratiquer la psychanalyse en utilisant la notion de différence sexuelle, avec des instruments cliniques comme le complexe d'OEdipe, est aussi aberrant que de prétendre la terre plate. Le temps est venu de sortir les divans sur les places, collectiviser la parole, politiser les corps, débinariser la sexualité et décoloniser l'inconscient : la survie de la psychanalyse est à ce prix. »-- Quatrième de couverture.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; discours dominant; fem7000; identités LGBTQIA2+; patriarcat; personnes trans*; sciences humaines; systèmes d'oppressions; thématiques; violences; épistémologie

Épistémologies du Sud, pensées et féminismes décoloniaux latino-américains - Coenga-Oliveira, Danielle (Revue Possibles, 2019)
Keywords: approches et analyses; capitalisme; cours; discipline; féminisme décolonial; histoire et politique; pol4212; premier cycle; science politique; science politique et droit; sciences humaines; sofia; système colonial; systèmes d'oppressions; thématiques; violences; épistémologie

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge handbooks in philosophy, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice--one of the most important and ground-breaking subjects to have emerged in philosophy in recent years--refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap